ANALYSIS OF THE EFFECT OF SOCIAL MEDIA MARKETING AND PRICE ON CONSUMER PURCHASING DECISIONS (LITERATURE REVIEW OF MARKETING MANAGEMENT) - Adisthi May Syaputri; Krismawati Halawa; Meta Sekar Rahmadani (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
The rapid development of social media marketing in this digital era provides many alternative choices for potential customers. On the other hand, this makes the level of business competition even tighter and various efforts are made by entrepreneurs to win the hearts of their consumers. One of the strategies used is marketing through social media or social media marketing (SMM). This research aims to review articles that discuss the influence of social media marketing and price on purchasing decisions. The results of the literature review articles in this study are 1) Social media marketing affects purchasing decisions, 2) Price has an effect on purchasing decisions